EFFECTIVENESS OF NEURO-MUSCULAR ELECTRICAL STIMULATIONS (NMES) IN REDUCING SUBLUXATION OF THE SHOULDER AFTER STROKE: RANDOMIZED CONTROLLED EXPERIMENTAL STUDY (International Journal of Physiotherapy, 2019)
Background: Shoulder subluxation in stroke is one of the most common and challenging squeals. Shoulder subluxation limits the patient’s daily activities, and it may lead to permanent disability. NMES (NeuroMuscular Electrical Stimulation) had been studied widely on shoulder subluxation with controversial results, but no evidence is reported of its effectiveness in shoulder subluxation. As NMES helps in producing strong contraction and thereby helps in improving the strength of the muscles and as it also helps in learning to contract appropriate muscles, this study was made to examine the Effectiveness of Electrical Stimulations in reducing Subluxation of the Shoulder after Stroke.Method: Study design, A Randomized control experimental design of 30 subjects. Subjects were randomly assigned into two groups, experimental (NMES group) and control (Non-NMES group) with 15 subjects in each group. Outcome measures were taken before and after the intervention on both the groups by using ‘Pain Estimation Scale’ (PES), 'Subluxation Grading’ by X-rays (AP view) and upper arm section of ‘Motor Assessment Scale’(MAS). Experimental group electrodes were placed over posterior deltoid and supraspinatus. Treatment time was 30 mints two times a day for five days in a week and six weeks.Results: Comparison of electrical stimulation with non-electrical stimulation was done by considering the differences of pre and post treatments in both groups and significance is observed by using independent sample t-test. Statistical analysis proved that there was significant (p